Police at the station and they don't look friendly : a Detective Sean Duffy novel - McKinty, Adrian (Seventh Street Books, an imprint of Prometheus Books, 2017)
"As he investigates a bizarre killing with an unusual weapon, Detective Sean Duffy only narrowly escapes becoming the next victim of the sinister underworld of 1980s Belfast"--